Targeted therapies for triple-negative breast cancer - Sousa, Márcio Filipe Magalhães de (2020)
Triple-negative breast cancer (TNBC), a heterogeneous and complex disease entity, lacks targeted therapies due to the absence of common therapeutic targetable features that exist in other types of breast cancer (BC). TNBC patients generally respond very well to standard chemotherapy, but when TNBC recurs is often very hard to treat. In this project, we aimed at improving TNBC targeted therapy via two conceptually different approaches. The first one consisted of the identification of essential genes for the survival of TNBC cancer cells under hypoxia, where we hypothesized that inactivation of such genes would be then synthetic lethal with antiangiogenic therapies. Thus contributing to the improvement of this class of drugs to which patients often acquire resistance. In the second part of this project, we aimed at exploring senescence as a vulnerability in cancer cells that can be therapeutically targeted using a one-two punch model. In a first step senescence is induced via a combination of Palbociclib (CDK4/6 inhibitor) treatment with Cyclin-dependent kinase 2 (CDK2) impairment; and in a second step, TNBC induced senescence cells were treated with ABT-263, a senolytic agent that promotes apoptosis preferentially on senescence cells over non-senescence cells. With this project, we contributed not only to the so needed improvement of target therapies for TNBC patients but also to other tumors, once these different approaches can be extended to other cancer types